Study on the mantle discontinuity structures beneath Northeast China with time–frequency phase-weighted stacks of ambient noise correlations. Issue 3 (17th May 2019) - Li, Songlin; Huang, Jinli; Liu, Zhikun; Zhang, Yi
SUMMARY: In this study, we use continuous waveforms recorded by 258 seismic stations from permanent and temporary networks in Northeast China from September 2009 to August 2011. Using ambient noise cross-correlations and time–frequency phase-weighted stacking based on the S -transform, we retrieve the P waves reflected on 410-km and 660-km discontinuities, we employ a 3-D P- wave velocity model as references to make time–depth conversion and then obtain the lateral depth variations of the two mantle discontinuities. Our results show that beneath the Changbaishan volcano, the 410-km discontinuity is depressed and is relatively thin, indicating the presence of high-temperature materials above the discontinuity. This implies that the Changbaishan volcano formed by upwelling of mantle melting associated with dehydration of the subducting Pacific slab. In the southeast margin of the study region, the 660-km discontinuity is depressed by ∼21 km, indicating the existence of low-temperature materials above the discontinuity. These results support the hypothesis that the Pacific slab has subducted beneath Northeast China and has stagnated at the bottom of the mantle transition zone. In addition, we determine that the 660-km discontinuity at 123.6°E–126.2°E, to the west of this stagnant slab, is slightly uplifted at a small scale, which may have been caused by upwelling melting formed by vertical tearing of the stagnant slab. Moreover, we preliminarily investigate the discontinuities beneath the northern part of the study region. The results show that the 410-km discontinuity is significantly depressed beneath the northeastern margin of the study region, which we attribute to reflected P -wave signals on the boundary between hydrous and anhydrous wadsleyite. The large-scale depression of the 660-km discontinuity observed beneath the northeastern part of the study region may be related to the existence of the stagnant slab.